Examining problem gambling, substance use disorders and cluster B personality traits among incarcerated individuals - Lind, Kalle; Palomäki, Jussi; Castrén Sari (Elsevier Ltd, 2025)
Prison populations face heightened rates of addictive behaviors and significant stressors, including health challenges and social disparities. Although problem gambling is prevalent in criminal justice settings, its distinctiveness compared to other addictions among incarcerated individuals remains uncertain. This study examines risk factors associated with problem gambling in Finnish prisoners and explores differences compared to other forms of addiction. Covariates from a questionnaire (N = 527) included gender, age, education, offender status, involvement in theft or property crime, Trauma Screening Questionnaire (TSQ), Depression Scale (DEPS), and lifetime abuse experiences. Of the 527 participants, 330 were interviewed using the Structured Clinical Interview (SCID-II) to assess personality disorders. Multiple logistic regression models were utilized, with separate models for problem gambling (PG), lifetime substance use disorder, and lifetime alcohol disorder. Crime type was not significantly associated with alcohol or substance use problems, but PG was associated with property crime or theft convictions. Borderline personality traits were linked to probable PG, while antisocial traits were linked to drug use, and both traits predicted alcohol misuse. Age and gender were significant only in relation to alcohol use problems, with older age and male gender indicating higher risk. The association between problem gambling and criminal behavior underscores the vulnerability of incarcerated individuals across various domains. Detailed assessments, considering the nature of criminal activity and personality disorders, especially borderline traits and comorbid conditions, are crucial for tailoring rehabilitation and treatment strategies to prevent recidivism. These findings provide valuable insights for clinicians managing addiction and mental health issues within correctional settings.